Penyuluhan Budidaya Padi Ladang Varietas Unggul Di Desa Efi-Efi Kecamatan Tobelo Selatan - Ariance Yeane Kastanja; Zeth Patty; Nonice Manikome; Zakarias Dilago (Universitas Teuku Umar, 2020)
This community service activity is carried out in the Efi-Efi Village, South Tobelo District, with the aim of providing skills and knowledge to farmers both about the use of high yielding variety of upland rice seeds and good upland rice cultivation techniques. The method used in this service is counseling about the cultivation of upland rice, the provision of high yielding variety of upland rice seeds and agricultural equipment and the making of high yielding variety of upland rice demonstration plots. Participants in this activity are the farmer women's group Efi-Efi, amounting to 20 members, who have been planting upland varieties of local upland rice. The results of the evaluation of community service activities showed that the knowledge and skills of the groups of women farmers who cultivated field rice had increased, and farmers accepted the use of high yielding variety of upland rice seeds introduced to them. In addition, there has also been a change in understanding in terms of shifting cultivation as has been done so far.